«АЛПАМЫС» ҲӘМ «МАНАС» ДӘСТАНЛАРЫНДА ОБРАЗЛАР УҚСАСЛЫҒЫ - Бекмурза улы, Азиз (FAN va JAMIYAT, 2025)
This article examines in detail the similarities in the creation of images in the Karakalpak folk epic «Alpamiys» and the Kyrgyz epic «Manas». The compositional structure, plot lines, and characterizations of these works are examined.